Optimization of Zakat as a Fiscal Policy Instrument for the Welfare of the Indonesian People - Rahmaniya, Salsa; Wardatul Fuadah, Irma; Sulalah, Sulalah; Raya Argantara, Zaid (Surau Journal of Islamic Studies, 2025)
This study examines the optimization of zakat as a fiscal policy instrument to support the welfare of the people in Indonesia. As one of the core pillars of Islam, zakat has significant potential to reduce poverty and promote social welfare equity in Indonesia, the world’s largest Muslim-majority country. However, despite its considerable potential, zakat management often falls short due to challenges in distribution efficiency, coordination among zakat institutions, and limitations in human resources and supporting infrastructure. This research explores how zakat can be integrated into national fiscal policies by strengthening existing management systems, enhancing transparency, and encouraging public participation in its distribution. Additionally, the study highlights the crucial role of zakat institutions, such as the National Amil Zakat Agency (BAZNAS), in directing zakat funds to productive sectors that empower recipients (mustahiq) and reduce economic disparities. By leveraging information technology and fostering greater synergy between zakat institutions and the government, zakat can be optimized as a fiscal instrument that not only aids in poverty alleviation but also contributes to inclusive economic growth. The study concludes that optimizing zakat as a component of fiscal policy can have a significant impact on improving the overall welfare of Indonesian society.